Comparative evaluation of the material of the artificial levees: A case study along the Tisza and Maros Rivers, Hungary - Sheishah, Diaa; Sipos, György; Barta, Károly; Abdelsamei, Enas; Hegyi, Alexandru; Onaca, Alexandru; Abbas, Abbas M. (Journal of Environmental Geography, 2023)
Artificial levees have major importance in protecting human lives and infrastructure as they are essential elements of the flood protection measures. Nevertheless, the lack of the necessary information about their structure and internal composition might cause high risks. To monitor their stability, integrated surveys are needed, including geophysical and geotechnical methods. Levees along the rivers in Hungary were constructed more than 150 years ago, and they were heightened several times; therefore, investigations are required to assure their performance in flood risk mitigation. Our investigation aimed to utilise non-invasive geophysical techniques, primarily electrical resistivity imaging, with the validation of geotechnical investigations to map and compare the compositional and structural variations of two very different levee sections along River Tisza and River Maros. Integrating the analysed drilling data with ERT profiles showed that the main composition of the investigated Tisza levee section is fine and medium silt with an average resistivity 30 Ωm, however, the investigated section of Maros levee was built of not only of fine and medium silt but also of medium and coarse sand exhibiting higher resistivity values reaching up to 2200 Ωm. Several physical parameters were measured to study the nature of constituting levee materials like moisture content, grain-size, porosity, bulk-density, saturated hydraulic conductivity, and resistivity. It was found that most of them show a connection with resistivity, but the hydraulic conductivity did not show a direct connection, however the latter could exhibit the aquitard nature of Tisza levee materials and the non-aquitard nature of Maros levee materials.